2017
DOI: 10.1158/1078-0432.ccr-16-1686
|View full text |Cite
|
Sign up to set email alerts
|

SMAD4 Loss Is Associated with Cetuximab Resistance and Induction of MAPK/JNK Activation in Head and Neck Cancer Cells

Abstract: Purpose We previously demonstrated an association between decreased SMAD4 expression and cetuximab resistance in head and neck squamous cell carcinoma (HNSCC). The purpose of this study was to further elucidate the clinical relevance of SMAD4 loss in HNSCC. Experimental Design SMAD4 expression was assessed by immunohistochemistry in 130 newly diagnosed and 43 recurrent HNSCC patients. Correlative statistical analysis with clinicopathological data was also performed. OncoFinder, a bioinformatics tool, was use… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 60 publications
2
49
0
Order By: Relevance
“…A recent study in head and neck squamous cell carcinoma showed genomic SMAD family member 4 (SMAD4) alterations in PDX . Surprisingly, SMAD4 loss has been shown to negatively correlate with cetuximab sensitivity, which is not in agreement with the conclusions of previous studies . These results further raise the possibility that the effects of genomic alterations upon drug responses in PDXs can vary.…”
Section: Aggressive Phenotypes and Variable Drug Sensitivitymentioning
confidence: 63%
“…A recent study in head and neck squamous cell carcinoma showed genomic SMAD family member 4 (SMAD4) alterations in PDX . Surprisingly, SMAD4 loss has been shown to negatively correlate with cetuximab sensitivity, which is not in agreement with the conclusions of previous studies . These results further raise the possibility that the effects of genomic alterations upon drug responses in PDXs can vary.…”
Section: Aggressive Phenotypes and Variable Drug Sensitivitymentioning
confidence: 63%
“…In the same vein, JNK also can modulate resistance to 5-fluorouracil (5-FU) in CRC by enhancing BCL2 phosphorylation and autophagy, which protect against 5-FU induced apoptosis [85]. Such modulatory effects of JNK on responses to chemotherapies and targeted therapies were also observed in gastric cancer [86], hepatocellular carcinoma [87], head and neck cancer [88], endometrial cancer [89], and ovarian cancer [90]. An interesting finding in this context is that JNK signaling seems specifically important for the maintenance of cancer stem cells in different cancer types including pancreatic [91], endometrial [92], and ovarian cancer [93].…”
Section: Jnk Enhancing Resistance To Erk Pathway Inhibitors and Chemomentioning
confidence: 96%
“…Cetuximab, an EGFR-blocking antibody, is currently the only approved EGFR-targeting therapy for patients with metastatic HNSCC (6,7). The efficacy of cetuximab is limited by intrinsic and acquired drug resistance, which is due mainly to tumor heterogeneity and genetic instability; these lead to constitutive activation of EGFR downstream signaling pathways and functional redundancy or compensatory activation of alternative growth factor receptor pathways (8)(9)(10)(11)(12)(13)(14). The current response rate to cetuximab as a single agent in HNSCC is only approximately 13% (15).…”
Section: Introductionmentioning
confidence: 99%